THE LEGAL FORCE OF THE TANAHKU TOUCH APPLICATION IN ENSURING THE DISCLOSURE OF LAND INFORMATION TO ELECTRONIC CERTIFICATE HOLDERS - Dhini Kusumaning Widyastuti; Rahmatul Hidayati (SOSIOEDUKASI, 2026)
The digitalization of Indonesia’s land administration system through the Sentuh Tanahku application represents a strategic government initiative to establish public services that are transparent, efficient, and based on legal certainty. The background of this study stems from the need to ensure transparency of land information and legal protection for land rights holders in the era of digital transformation. The research focuses on two main issues: the legal framework governing electronic land registration through the Sentuh Tanahku application and the legal force of electronic land certificates for land rights holders. This study is significant because the transition from a conventional to a digital system requires a strong legal foundation to ensure the continued protection of citizens’ land rights. This research employs a normative legal method using both the statutory approach and the conceptual approach. The legal materials used include Law Number 5 of 1960 concerning the Basic Agrarian Law (UUPA), Government Regulation Number 24 of 1997 on Land Registration, Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 on Electronic Information and Transactions (ITE), Law Number 14 of 2008 on Public Information Disclosure, and Ministerial Regulations of ATR/BPN Number 1 of 2021 and Number 3 of 2023.The findings indicate that electronic land registration in Indonesia has a strong and integrated legal foundation, with constitutional legitimacy rooted in Article 33 paragraph (3) and Article 28D paragraph (1) of the 1945 Constitution. The electronic land certificate (e-certificate) holds the same evidentiary power as a physical certificate, provided it meets the elements of authenticity, integrity, and data reliability as regulated in Ministerial Regulation ATR/BPN Number 1 of 2021 and the ITE Law. Meanwhile, the Sentuh Tanahku application serves as a tool for implementing the principle of public information transparency (Articles 9 and 11 of the Public Information Disclosure Law), while maintaining data privacy protection in accordance with Law Number 27 of 2022.